Macrophage migration inhibitory factor mediates the antidepressant actions of voluntary exercise - Moon, Hyo Youl (National Academy of Sciences, 2012)
Voluntary exercise is known to have an antidepressant effect. However, the underlying mechanism for this antidepressant action of exercise remains unclear, and little progress has been made in identifying genes that are directly involved. We have identified macrophage migration inhibitory factor (MIF) by analyzing existing mRNA microarray data and confirmed the augmented expression of selected genes under two experimental conditions: voluntary exercise and electroconvulsive seizure. A proinflammatory cytokine, MIF is expressed in the central nervous system and involved in innate and adaptive immune responses. A recent study reported that MIF is involved in antidepressant-induced hippocampal neurogenesis, but the mechanism remains elusive. In our data, tryptophan hydroxylase 2 (Tph2) and brain-derived neurotrophic factor (Bdnf) expression were induced after MIF treatment in vitro, as well as during both exercise and electroconvulsive seizure in vivo. This increment of Tph2 was accompanied by increases in the levels of total serotonin in vitro. Moreover, the MIF receptor CD74 and the ERK1/2 pathway mediate the MIF-induced Tph2 and Bdnf gene expression as well as serotonin content. Experiments in Mif(−/−) mice revealed depression-like behaviors and a blunted antidepressant effect of exercise, as reflected by changes in Tph2 and Bdnf expression in the forced swim test. In addition, administration of recombinant MIF protein produced antidepressant-like behavior in rats in the forced swim test. Taken together, these results suggest a role of MIF in mediating the antidepressant action of exercise, probably by enhancing serotonin neurotransmission and neurotrophic factor-induced neurogenesis in the brain.